Protein quality in lines and experimental hybrids of QPM. Central Highlands, Mexico - Arellano-Vázquez, José Luis (2021)
Introduction. Currently, maize is the most cultivated grain in the world and it is feasible to improve the nutrition of its consumers through the development of quality protein maize (QPM), whose basis is the expression of the opaque2 gene, which increases the contents of lysine and tryptophan in the grain. Objective. To analyze chemically the protein of the grain of lines and experimental simple hybrids of QPM and to know the relationships between the genotype and the evaluated variables of protein quality. Materials and methods. The experiments were carried out during 2017 in the Interdisciplinary Professional Unit of Biotechnology of the Instituto Politecnico Nacional (Mexico City). Whole grains of parental lines (P1 to P6) and direct simple hybrids were used. Lysine, tryptophan, and protein quantity and quality were estimated. A completely randomized design with three replications was used. Analysis of variance, comparison of means, and principal component analysis were performed. Results. Lines P2, P3, and P6, and hybrids P2 x P4 and P2 x P6 were identified as significant (p ² 0.05) QPM. The protein quality index was correlated with tryptophan (r = 0.9 *) and with lysine (r = 0.7 *) but not with total protein. Conclusions. The fundamental factor for developing the QPM were the essential amino acids and the limiting factor for increasing their nutritional value was the quality of the protein.